2018
DOI: 10.17016/feds.2018.058
|View full text |Cite
|
Sign up to set email alerts
|

Oil, Equities, and the Zero Lower Bound

Abstract: From late 2008 to 2017, oil and equity returns were more positively correlated than in other periods. In addition, we show that both oil and equity returns became more responsive to macroeconomic news. We provide empirical evidence and theoretical justification that these changes resulted from nominal interest rates being constrained by the zero lower bound (ZLB). Although the ZLB alters the economic environment in theory, supportive empirical evidence has been lacking. Our paper provides clear evidence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…10 This evidence suggests that there cannot be indirect feedback from exogenous exchange 10 Fratzscher et al (2014) confirmed these results using more recent data. Datta et al (2019), using a much smaller set of U.S. macroeconomic news than Kilian and Vega (2011) and restricting attention to the response of the price of oil to these news within the same day, show that during the six years when the zero-lower bound was binding, two of twelve news variables had a much larger effect on the price of oil than reported in Kilian and Vega (2011). Unlike Kilian and Vega (2011), however, Datta et al do not report data-mining robust p-values, making it impossible to judge the statistical significance of their estimates, and the 2 R of their regression including all twelve predictors is only 3%, so the extent of the feedback appears negligible even during the zero-lower bound period.…”
Section: Restrictions On the Feedback From Real Interest Rate And Reamentioning
confidence: 99%
“…10 This evidence suggests that there cannot be indirect feedback from exogenous exchange 10 Fratzscher et al (2014) confirmed these results using more recent data. Datta et al (2019), using a much smaller set of U.S. macroeconomic news than Kilian and Vega (2011) and restricting attention to the response of the price of oil to these news within the same day, show that during the six years when the zero-lower bound was binding, two of twelve news variables had a much larger effect on the price of oil than reported in Kilian and Vega (2011). Unlike Kilian and Vega (2011), however, Datta et al do not report data-mining robust p-values, making it impossible to judge the statistical significance of their estimates, and the 2 R of their regression including all twelve predictors is only 3%, so the extent of the feedback appears negligible even during the zero-lower bound period.…”
Section: Restrictions On the Feedback From Real Interest Rate And Reamentioning
confidence: 99%
“…3 In this spirit, Wieland (2017) rejects the liquidity trap hypothesis by showing that negative productivity shocks (earthquakes, oil price shocks) are contractionary even at the zero lower bound. In contrast, Datta et al (2017) find strong co-movements between oil and equity returns at the zero lower bound, which is supportive of the liquidity trap hypothesis. Even if the issue is not yet empirically settled, it remains that the impact of supply shocks at the zero lower bound provides a clean test of the feedback loop described in Chart 1.…”
Section: Low Future Inflationmentioning
confidence: 51%
“…Our contribution relative to all these papers is to introduce the ZLB and to focus on the recent changes since the Great Recession started. The contemporaneous studies by Nakata and Tanaka (2016), Datta et al (2018), and Bilal (2017) are also closely related, with a somewhat similar message but differences in empirical work and theoretical model.…”
Section: Related Literaturementioning
confidence: 86%